Exploration of the Readiness of Indonesian MSMEs in Facing Digital Taxes and Their Implications for Tax Justice - Suleman, Nurjana; Ngabito, Dewi; Sholehah, Nur Lazimatul Hilma (University of Merdeka Malang, 2024)
The Indonesian government has adopted a digital tax policy in response to accelerating digital transformation aimed at increasing state revenue from digital economy transactions. However, this policy also brings new challenges for micro, small, and medium enterprises (MSMEs), which are the pillars of Indonesia's economy. This study examines the readiness of MSMEs in Indonesia to face digital taxation challenges and analyzes their impact on the perception of tax justice. This study uses a quantitative method with data collection through questionnaires. The population studied is MSMEs that use digital platforms in Gorontalo. Samples were selected using the purposive sampling method. The data analysis technique is a structural equation model (SEM) with Smart PLS 3.0 software. The study results show that understanding digital taxes and tax technology infrastructure positively affects digital tax compliance. In addition, understanding digital taxes also positively impacts the perception of digital taxes. However, tax technology infrastructure and digital tax compliance do not positively influence tax perception. The influence of understanding digital taxes and tax technology infrastructure on digital tax perceptions is largely mediated by digital tax compliance. Technology adaptation moderates the relationship between digital tax understanding and tax technology infrastructure to the perception of tax justice. However, the effect of technology adaptation moderation on the relationship between digital tax understanding and tax technology infrastructure and the perception of tax justice is insignificant.